The promises of educational neuroscience: examples from literacy and numeracy. (3rd July 2019) - Kwok, F. Y.; Ansari, D.
ABSTRACT: This commentary reviews and summarises the strides which neuroscience has made in our present understanding of the development of literacy and numeracy in children. Specifically, it draws attention to key insights from studies which have elucidated the possible neural mechanisms that may account for difficulties in the development of these fundamental learning abilities. It also discusses the possible future applications of neuroscience in providing early detection of these learning difficulties in children, and in guiding the design of appropriate interventions aimed at mitigating these difficulties. Finally, it identifies challenges that will arise as the field of educational neuroscience matures. Importantly, it emphasises that educational neuroscience research must be considered in tandem with research in other fields in order to develop a holistic understanding of the process of learning.